Writing Scenes in the Correspondence of Catharina Regina von Greiffenberg and Sigmund von Birken. - Andersen, Sonja M. (Feminist German Studies, 2025)
This article focuses on the writing practices and correspondence of Catharina Regina von Greiffenberg (1633–1694), a Protestant poet in predominantly Catholic 17th-century Austria. It examines her extensive letter exchange with the literary figure Sigmund von Birken, highlighting how their epistolary relationship reveals Greiffenberg’s daily writing scenes, creative process, and efforts to sustain her devotional mission, Deoglori ("glory to God"), amid social, religious, and personal challenges. The letters provide insight into her balancing of literary production, family duties, and religious activism, while also illustrating the collaborative and performative nature of early modern writing. This correspondence is presented as a valuable resource for understanding Greiffenberg’s unique style and the broader cultural context of women’s writing in the Baroque period.